Estudio cualitativo sobre el rol de madres y padres de estudiantes universitarios no tradicionales como habilitadores de trayectorias educativas (Praxis Educativa, 2026)
This study aimed to explore the role of mothers and fathers as facilitators in the educational trajectories of first-generation university students (FGUs) in Chile. Using qualitative methodology and a phenomenological approach, seven FGUs mothers and fathers were interviewed. The analysis highlights that one of the most relevant aspects is the different forms of participation according to gender roles. Mothers tend to play a socio-affective role, which includes providing emotional support and constant care. Furthermore, during the school years, they have a greater presence in school activities and participate in them.
Keywords: Higher education; Universitary student; Family role; Gender role; Educational policy